2009
DOI: 10.1175/2009jas3165.1
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Eddy Feedback and the Persistence of the Zonal Index in an Idealized Atmospheric Model

Abstract: An idealized atmospheric model is employed to quantify the strength of the eddy feedback and the persistence of the zonal index. The strength of the surface frictional damping on the zonal index is varied, and an external zonal momentum forcing is included to compensate for the momentum change associated with the friction change such that the climatological jet latitude and shape are unchanged.The model can generate a nearly identical climatology and leading mode of the zonal mean zonal wind for different fric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
56
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 34 publications
5
56
0
Order By: Relevance
“…2b) is nearly indistinguishable from that of the simulated z. This is consistent with the findings of Chen and Plumb (2009), who showed that frictional damping of the zonal index is well captured in an idealized model by projecting the annular mode/ zonal index pattern onto the lower-layer friction.…”
Section: B Internal Variabilitysupporting
confidence: 89%
See 3 more Smart Citations
“…2b) is nearly indistinguishable from that of the simulated z. This is consistent with the findings of Chen and Plumb (2009), who showed that frictional damping of the zonal index is well captured in an idealized model by projecting the annular mode/ zonal index pattern onto the lower-layer friction.…”
Section: B Internal Variabilitysupporting
confidence: 89%
“…These modes are associated with a mass exchange between middle and high latitudes, producing a meridional seesaw in sea level pressure and a north-south displacement of the eddy-driven jet and extratropical storm tracks. Similar variability patterns are also found in a variety of atmospheric models, ranging from quasigeostrophic models (Lee and Feldstein 1996;Zhang et al 2012) to idealized primitive equation models (Gerber and Vallis 2007;Chen and Plumb 2009) to comprehensive general circulation models (Gerber et al 2008). It has also been noted that the atmospheric response to external forcing projects strongly on this mode of variability for many types of forcing (Yin 2005;Son et al 2008b).…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…One consequence of this is that the autocorrelations of the leading principal components (PCs) corresponding to the individual EOFs do not decay exponentially but show some oscillatory characteristics. This behavior, in turn, cautions against using simple paradigms based on stochastically forced, single component, systems as a basis for estimating eddy feedback strength (e.g., Lorenz andHartmann 2001, 2003;Watterson 2007;Chen and Plumb 2009) or for estimating the sensitivity of the system to climate perturbations (Gerber et al 2008;Ring and Plumb 2008). Such questions are addressed here by application of theory to results from a dry, dynamical core, global model run in a simplified solsticial configuration.…”
Section: Introductionmentioning
confidence: 99%